2011
DOI: 10.1182/blood.v118.21.5058.5058
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Implications of Nucleated Red Blood Cells in Myelodysplastic Syndrome

Abstract: 5058 Background: The presence of elevated nucleated red blood cells (NRBC) in the peripheral blood smear points towards the presence of myelodysplastic syndrome (MDS) or myelophthisis. The intent of our study was to assess the prognostic implication of the presence of increased NRBC in patients with MDS. Methods: Retrospective single institution chart review over a period of 10 years from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The positive correlation between erythropoietin levels and the amount of PBCECs also suggests the potential contribution of stress erythropoiesis to the expansion of CECs in autoinflammatory diseases. Several studies have reported that the expansion of PBCECs was related to a high mortality or disease severity 5 , 7 9 . Macrophage activation syndrome, an extremely severe manifestation of systemic inflammation with cytokine storm, occurs more frequently in SoJIA than in KD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive correlation between erythropoietin levels and the amount of PBCECs also suggests the potential contribution of stress erythropoiesis to the expansion of CECs in autoinflammatory diseases. Several studies have reported that the expansion of PBCECs was related to a high mortality or disease severity 5 , 7 9 . Macrophage activation syndrome, an extremely severe manifestation of systemic inflammation with cytokine storm, occurs more frequently in SoJIA than in KD.…”
Section: Discussionmentioning
confidence: 99%
“…CECs thus cannot be found in the peripheral blood of healthy infants, children, or adults. Peripheral blood CECs (PBCECs) have been observed in pathological settings of hematological disorders 5 , solid tumors 6 , acute respiratory distress syndrome 7 , cardiovascular diseases 8 , and sepsis 9 . Many studies have mentioned the link between increased numbers of PBCECs and serious conditions or poor prognoses 5 9 .…”
Section: Introductionmentioning
confidence: 99%